Synthesis and characterisation of sesquioxidic precipitates formed by the reaction of acid mine drainage with fly ash leachate - Burgers, C. L. (Colleen Lucie) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric)--University of Stellenbosch, 2003.